Identification of Adenovirus (Ad) Penton Base Neutralizing Epitopes by Use of Sera from Patients Who Had Received Conditionally Replicative Ad (Addl1520) for Treatment of Liver Tumors - Hong, Saw See (American Society for Microbiology, 2003)
Sera from 17 patients with primary and secondary liver tumors who had been administered oncolytic adenovirus (Ad) mutant Addl1520 were analyzed for anti-Ad neutralization titers and antibodies to the Ad major capsid proteins hexon, penton base (Pb), and fiber. The antibodies recognized mainly conformational epitopes in hexon and both linear and conformational epitopes in Pb and fiber. Pb-specific antibodies were isolated from serum samples that had been obtained prior to and during the course of the treatment of four of these patients. We found that the Pb antibodies had a significant contribution toward anti-Ad neutralization, and this mainly occurred at the step of virus internalization. The Pb antigenic epitopes were determined by phage biopanning and were mapped to 10 discrete regions, which made up three major immunodominant domains within residues 51 to 120, 193 to 230, and 311 to 408, respectively. One of these domains (residues 311 to 408) overlapped the highly conserved, integrin-binding RGD (Arg-Gly-Asp) motif. The contribution of antibodies directed to RGD and other epitopes in Ad neutralization activity was determined indirectly by using a phage-mediated depletion assay. Our results suggested that circulating RGD antibodies were not prevalent and were poorly neutralizing and that other peptide motifs within residues 51 to 60, 216 to 226, and 311 to 408 in Pb sequence represented major target sites for neutralizing antibodies.